How does artificial intelligence influence the socio-economic performance of companies in the European Union? - Ramona Pîrvu; Daniela-Melania Mihai; Nicolae Ecobici; Maria-Eliza Antoniu; Irina Elena Chirtoc; Gabriela Bușan (Amfiteatru Economic Journal, 2024)
The main objective of the proposed study is to analyse how the implementation of Artificial Intelligence (AI) systems can influence the socio-economic performance of companies across different sectors in the European Union. In this context, we selected and processed companies data from 27 EU Member States, operating in nine main sectors of activity. For the measurement of social performance, we used as indicators the number of employees and hours worked per employee, and for the measurement of economic performance, we used the net turnover and the added value of the company. The study's originality lies in its concurrent analysis of the impact of AI on both the economic and social performance of firms across nine sectors. The robust regression method with S estimator was applied to address the research objective. The results indicate a reduction in the number of employees and hours worked per employee following the implementation of AI in sectors such as manufacturing, accommodation and food services, and transportation. Regarding the economic performance of firms, the study's findings confirm the positive impact of AI implementation on the value added of firms in the manufacturing, transportation, trade, and water supply and waste management sectors, as well as on the increase in turnover of firms operating in the construction, transportation, information and communication technology, and trade sectors. The analysis conducted may contribute to guiding decisions in the technological and economic domains to support innovation and competitiveness of European enterprises in specific fields of activity.
Keywords: O36; L25; J21; 330; added value of the companies; Artificial Intelligence; net turnover of the company; number of employees; number of hours per employee; sectors of activity